Transformation of Wives’ Roles in the Household: A Socio-Legal Study of Gender and Indonesian Family Law in Padangsidimpuan - Ikhwanuddin Harahap (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
The transformation of wives’ roles in Indonesian Muslim families has undergone significant changes alongside the increasing participation of women in education and economic activities. However, these changes often remain inconsistent with the normative construction of family law, which continues to reflect patriarchal values. This study aims to analyze the transformation of wives’ roles in households in Padangsidimpuan City through the lens of Amina Wadud’s gender perspective and Indonesian positive law, while identifying the gap between legal norms and evolving social practices. The research employs a socio-legal approach, utilizing interviews, observations, and documentary analysis of legal regulations, particularly Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law. The findings reveal that the transformation of wives’ roles occurs gradually and asymmetrically. Women’s increasing economic contributions have strengthened their bargaining position in family decision-making processes, particularly regarding children's education, financial management, and family planning. Nevertheless, patriarchal values persist, resulting in role ambivalence and a double burden for women. The study also identifies a gap between law in books and law in action, where legal norms have not fully accommodated the social realities evolving toward more egalitarian partnerships. These findings imply the need for a more contextual, gender-responsive, and substantively just reconstruction of Islamic family law. Furthermore, this study contributes to the development of socio-legal studies, gender studies, and Islamic family law scholarship by demonstrating how the interaction between legal norms, religious interpretations, and social practices shapes the transformation of gender relations within contemporary Muslim families in Indonesia.